Rare NF1 microdeletion syndrome in an Omani patient. Issue 12 (26th October 2018) - Al‐Araimi, Musallam; Hamza, Nishath; Al Yahmadi, Ali; Al Mazrooey, Hiba; Elsheikh, Afaf; Al Amri, Amira; Al Harrasi, Salma; Hausdorf, Lena; Mula‐Abed, Waad‐Allah
Key Clinical Message: Neurofibromatosis‐1 phenotype combined with webbed neck and short stature in a young Omani patient was revealed to be due to a de novo germ‐line heterozygous 1.7 Mb microdeletion at 17q11.2. This lead to the diagnosis of NF1 microdeletion syndrome. Abstract : Neurofibromatosis‐1 phenotype combined with webbed neck and short stature in a young Omani patient was revealed to be due to a de novo germ‐line heterozygous 1.7 Mb microdeletion at 17q11.2. This lead to the diagnosis of NF1 microdeletion syndrome.